2005
DOI: 10.1097/01.tp.0000181194.42642.97
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lymphocyte Cultures Can Predict TCR Vβ Repertoires of T Cells Infiltrating Kidney Transplants during Acute Rejection Episodes

Abstract: Alloreactive T cell populations can show skewing of T-cell antigen receptor (TCR) Vbeta gene usage. The aims of the experiments were to compare in vivo and in vitro T cell alloresponses against donor alloantigens for TCR Vbeta gene usage. T-cell cultures from renal biopsies taken during acute rejection and pretransplant mixed lymphocyte cultures (MLC) were established from five renal transplant patients. TCR Vbeta gene usage, assessed with Vbeta family specific antibodies, showed that up to five different Vbet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Prior characterization of TCR repertoires by cruder spectratyping-based approaches demonstrated that the expansion of alloreactive GIL clones was not mirrored in the peripheral blood, resulting in a clear distinction in TCR repertoires of oligoclonal tissue-derived and more broadly distributed blood-derived T-lymphocyte populations. 13,15,16,23-25,32-35 Our NGS-based TCR repertoire analysis confirms this phenomenon, in agreement with an earlier study. 18 In greater detail, we now show further that tissue- and blood-derived TCR repertoires have distinct clonal compositions that remain consistent over time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior characterization of TCR repertoires by cruder spectratyping-based approaches demonstrated that the expansion of alloreactive GIL clones was not mirrored in the peripheral blood, resulting in a clear distinction in TCR repertoires of oligoclonal tissue-derived and more broadly distributed blood-derived T-lymphocyte populations. 13,15,16,23-25,32-35 Our NGS-based TCR repertoire analysis confirms this phenomenon, in agreement with an earlier study. 18 In greater detail, we now show further that tissue- and blood-derived TCR repertoires have distinct clonal compositions that remain consistent over time.…”
Section: Discussionsupporting
confidence: 92%
“…Alloreactive GILs are significantly enriched in graft tissues compared with peripheral blood, 15 even in the absence of histopathologically defined rejection. 18 Therefore, these T lymphocytes would be highly represented among the TCR clones in the tissue-derived repertoires and minimally among blood repertoires.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding and predicting BV usage bias in graft rejection could be clinically useful. Prediction of BV usage useful for therapeutic specificity by targeting only those BV families involved in rejection for deletion [ 14 , 30 ], rather than nonspecifically via agents such as OKT3. In genetically controlled animal transplant models, BV usage of alloreactive T cells is predictable [ 29 , 31 , 32 ] and stable over time [ 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%